2015
DOI: 10.1002/cbin.10459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the surface modification, size, and shape on cellular uptake of nanoparticles

Abstract: Nowadays successful application of nanoparticles for therapeutic objects needs the effective uptake of them by cells. Hence, studying of the interaction of nanoparticles with cell membrane for effective cellular uptaking seems to be vital and important. Trafficking of lipids, proteins, glucose, and other biomaterials into the cells is possible from two major exocytic and endocytic pathways. The penetration ability of nanoparticles into the cells must be considered in engineering of these particles. Enormous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
279
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 497 publications
(292 citation statements)
references
References 95 publications
(113 reference statements)
12
279
1
Order By: Relevance
“…In particular, surface modification can alter the extent and rate of cell entrance of NPs. For example, positive charges on the NPs increase electrostatic interaction with the negatively-charged membrane, thereby promoting cellular uptake (Salatin et al, 2015). In some instances, surface modification of NPs affects not only intracellular uptake, but also subcellular distribution inside the cell.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, surface modification can alter the extent and rate of cell entrance of NPs. For example, positive charges on the NPs increase electrostatic interaction with the negatively-charged membrane, thereby promoting cellular uptake (Salatin et al, 2015). In some instances, surface modification of NPs affects not only intracellular uptake, but also subcellular distribution inside the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor influencing the rate of absorption and uptake is the NP shape. This is related to the increase of the surface area to volume ratio for cylindrical or rod shapes with a consequent increase of the surface available for absorption to the membrane [24,71]. Moreover, it has been recently observed that the details of the NP surface topology have considerable effect on cellular uptake [21].…”
Section: Nanoparticle-membrane Interactions: Elastic Theorymentioning
confidence: 99%
“…Therapeutic agents can be encapsulated within nanoparticles or incorporated via surface adsorption or surface conjugation Salatin et al 2015b). The integration of therapeutic agents into the nanoparticles with desirable shape, size, and surface physicochemical characteristics imposes a significant effect on improving their solubility, circulation half-life, bio-distribution and reducing the immunogenicity (Sun et al 2014, Salatin et al 2015a.…”
Section: Nanoparticles Polymeric Nanoparticlesmentioning
confidence: 99%